Polimorfismo dos receptores Beta 3 adrenérgicos e sua correlação com a síndrome de bexiga hiperativa - Ferreira, Cristina Eustáquia [UNIFESP] (2011)
Objective: to evaluate if the polymorphism at codon 64 of the adrenergic 3 receptor gene with the replacement of a triptophan by Arginine represents a risk factor for the Hyperactive Bladder Syndrome. Casuistic and Methods: case study control involving 218 patients from the Climacteric Ambulatory and the Hyperactive Bladder Ambulatory. The case group comprised 49 patients who met the clinical criteria for the hyperactive bladder syndrome. Now, the control group comprised 169 patients without any type of urinary symptom. 5 ml of venous blood were collected from each participant in order to extract the genomic DNA, followed by the determination of the polymorphism by PCR. Results: The groups were heterogeneous regarding the IMC, V8 questionnaire, urinary frequency, nocturia, mictional urgency and family history of urgency urinary incontinence. The genotypic distribution for the control group was comprised of 128 savages (75.7%) 40 heterozygote (23.7%) and 01 Muted (0.6%). In the case group, 24 savages (49%), 25 heterozygote (51%) and none muted (p<0.05). The allelic analysis found was of 12.4% of muted genes for the controls and 25.5% for the cases (p<0.05). After multivariate logistic regression an OR of 3.23 (p<0.05) was found for those who present a family history of Urgency Urinary Incontinence of 3.11 (p<0.05) for those who present the polymorphism discussed here. Conclusion: The polymorphism at codon 64 of the adrenergic 3 receptor gene with the replacement of a triptophan by Arginine represents a risk factor for the Hyperactive Bladder Syndrome in the Brazilian population.